Auditory, Social, and Behavioral Skills of Children With Unilateral/Mild Hearing Loss. (13th December 2019) - Nassrallah, Flora; Tang, Ken; Whittingham, JoAnne; Sun, Huidan; Fitzpatrick, Elizabeth M
Abstract: This study explored the impact of mild bilateral or unilateral hearing loss on auditory, social, and behavior skills in early school-aged children. Thirty-two children (aged 5–9 years) were evaluated with parent and teacher questionnaires. Most outcomes were within the range of expected scores. However, functional auditory skills were below published results for children with typical hearing. On the social skills scale, about 21.4% (parent-reported) and 20.0% (teacher-reported) of children were below one standard deviation (SD) of the normative mean (i.e., a standard score below 85). On the parent-reported behavior test, over a quarter of children scored beyond 1 SD on some subscales. Laterality of hearing loss had no effect on outcomes (p > .05). Agreement between parents and teachers varied from poor (intraclass correlation coefficient [ICC]: .162) to moderate (ICC: .448). Results indicate that these children are functioning in most areas like their peers with typical hearing. Additional research on this population of children who may benefit from early identification and amplification is warranted.